(untitled) (Journal of Parents and Teachers, 2017)
We think of communication as a basis of exchange, knowledge, understanding and understanding. At a time when we think that adolescents know everything or a lot about sexuality, we discover in the listening hours of our workshops in Affective-Sexual Education, that despite the diversity of means and resources available to them, many of their fears, worries and concerns remain very similar to the sense and lived by many of us time ago. We believe that a rich communication that enables a dialogue through truth, spontaneity, naturalness and respect, will generate a climate of trust and security that will facilitate communication.